KEMAMPUAN RASIO KEUANGAN DALAM MEMPREDIKSI PERINGKAT OBLIGASI PADA PERUSAHAAN SEKTOR NON KEUANGAN - Partha, Made Bana; Yasa, Gerianta Wirawan (E-Jurnal Akuntansi; Vol 15 No 3 (2016), 2016)
User 15.00 This research aims to examine the ability of financial ratios (profitability, leverage, liquidity, solvability and productivity) to predict Pefindo’s bond ratings on company that listed in Indonesia Stock Exchange from 2010 until 2014. To solve the problems in this research, be used discriminant analysis because the dependent variable is a dummy. In discriminant analysis, show that profitability, leverage, solvability and productivity have ability to predict Pefindo’s bond ratings on company that listed in Indonesia Stock Exchange from 2010 until 2014. While the liquidity has not ability to predict the bond ratingson company that listed in Indonesia Stock Exchange from 2010 until 2014. Normal 0 false false false EN-US X-NONE X-NONE /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-parent:""; mso-padding-alt:0in 5.4pt 0in 5.4pt; mso-para-margin:0in; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:10.0pt; font-family:"Calibri","sans-serif"; mso-bidi-font-family:"Times New Roman";}
Keywords: bond ratings, financial ratios, discriminant